Mahārāshṭrāntīla vicāravanta : Ācārya Śã. Da. Jāvaḍekara, sāhitya sūcī - Kumbhāra, Nāgorāva, 1952- (Prabodhana Prakāśana, 1985)
Bibliography of the works of Śaṅkara Dattātraya Jāvaḍekara, 1894-1955, a nationalist, social worker, and Marathi author from Maharashtra.